Training and Making Guidelines for Organizing Hybrid Exhibitions - Tomy Andrianto; Any Ariani Noor; Ratna Padmi Trihartanty; Tamara Herlinda Erwin; Dinarsiah Chendraningrum; Sri Hastuti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Exhibition is a sub-sector of the creative economy and part of the tourism industry that developed well in Indonesia before Covid-19. Exhibition activities, which were actually gathering large numbers of people, became one of the industries hardest hit and even stopped completely, even though alternative technologies that facilitated online meetings began to develop at that time. Currently, after the handling of Covid-19 has improved considerably, the concept of hybrid exhibitions has begun to emerge and provides an alternative for industry players in conducting exhibitions. Unfortunately, many industry players do not understand how the concept of hybrid exhibitions does not try to completely replace conventional exhibitions. In addition, there is a need for training and guidance that will facilitate industry players in carrying out hybrid exhibitions. Community Service with this community partnership program (PKM) scheme helps ASPERAPI (Exhibition Organizer Association) DPD West Java as a partner in making Hybrid Exhibition Organizing Guidelines and training its members. Another objective is to provide additional skills and knowledge for ASPERAPI members in facing the challenges of present and future exhibition activities. The challenges facing partners today are how to restore business while at the same time reaching more audiences by utilizing hybrid technology/applications. The implementation method is mentoring, training and making guides with the outputs of intellectual property rights and scientific articles and service articles as activity reports.